The Dialogue between the Supreme Administrative Court and the Constitutional Tribunal in the Preliminary Reference Procedure - Chmielarz-Grochal, Anna (Teisė, 2020)
The purpose of the article is to analyze how the Supreme Administrative Court implements the right of this court to apply to the Constitutional Tribunal, enshrined in the Constitution of the Republic of Poland, with a request to examine the constitutionality of the legal act applicable in a particular case. The emergence of this investigation is marked by a noticeable decrease in the number of requests submitted by administrative courts to investigate the constitutionality of a legal act, which encourages the investigation of the causes of this phenomenon. The prior application of the court for the constitutionality of a legal act encourages the analysis of a specific cooperation dialogue between the requesting court and the Constitutional Tribunal.